2021
DOI: 10.1111/fwb.13866
|View full text |Cite
|
Sign up to set email alerts
|

Damming shapes genetic patterns and may affect the persistence of freshwater fish populations

Abstract: River damming threatens freshwater biodiversity worldwide by isolating populations, reducing both gene flow and genetic variation, and affecting the ability of a given population to adapt to environmental changes. Herein, we employed a microsatellite DNA marker panel and a multitemporal approach to assess the effects of damming on the genetic diversity of a long‐lived species from both contemporary and historical perspectives. To accomplish this, we used the migratory catfish Pseudoplatystoma corruscans as a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 157 publications
(163 reference statements)
0
4
0
Order By: Relevance
“…Within each species, we found populations with relative higher haplotype and nucleotide diversity, and populations with intermediate to low levels of one or both genetic diversity indices, independently from the latitudinal positioning of the inhabited river. The RDA analysis revealed some weak correlations between both nucleotide and haplotype diversity indices and some environmental characteristics, some of which are consistent with previous studies, which found correlations between genetic diversity and ecosystem size (i.e., river length in the RDA analysis [32]), habitat features (i.e., refuges and geology in this study [28]), and hydrological regime (represented in this study by the Q/A [92]). Although these results may suggest an influence of local environmental conditions on genetic variability, the RDA scores of both the genetic indices were too low to support a strong relationship between genetic variability and the environmental parameters.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Within each species, we found populations with relative higher haplotype and nucleotide diversity, and populations with intermediate to low levels of one or both genetic diversity indices, independently from the latitudinal positioning of the inhabited river. The RDA analysis revealed some weak correlations between both nucleotide and haplotype diversity indices and some environmental characteristics, some of which are consistent with previous studies, which found correlations between genetic diversity and ecosystem size (i.e., river length in the RDA analysis [32]), habitat features (i.e., refuges and geology in this study [28]), and hydrological regime (represented in this study by the Q/A [92]). Although these results may suggest an influence of local environmental conditions on genetic variability, the RDA scores of both the genetic indices were too low to support a strong relationship between genetic variability and the environmental parameters.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, genetic diversity, particularly in neutral (i.e., not under selection) DNA regions, such as those commonly used for population genetic studies, typically reflect historical demographic evolution due to past climatic and geological changes e.g., [28]. Nevertheless, both genetic and phenotypic variabilities can also be altered by recent anthropogenic activities such as the introduction of exotic species (e.g., following hybridization [29]) and river damming [30][31][32]. Thus, separating genetic and phenotypic variations induced by local adaptation developed during historical evolution from the variations deriving by relatively recent events, provides valuable insights for both eco-evolutionary processes and for a conservation perspective [33].…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with previous population genetic studies of Pseudoplatystoma . Similar levels of genetic diversity in P. corruscans samples obtained from Paraguay, Paraná and São Francisco basins have been reported before (Carvalho et al ., 2012; Dantas et al ., 2013; do Prado et al ., 2018; Machado et al ., 2022; Pereira et al ., 2009; Vaini et al ., 2016). Some of these studies reported population structure in the Upper Parana basin, consistent with the weak signal obtained in this study's results (F ST = 0.02 between samples from the Upper Paraná and Grande River sites).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the construction of the dam, the formerly separated populations have been able to hybridize, a likely explanation for the admixture of genetic clusters observed at sites 2‐RI and 3‐CAM, both upstream of the Itaipú reservoir. Other studies also reported that dam construction and alteration of the ecosystem results in changes in population effective sizes and genetic diversity in P. corruscans (Machado et al ., 2022). Given that P. corruscans undertakes long‐distance migrations during its life cycle, gene flow among formerly isolated populations is naturally expected when former geographic barriers are no longer present.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies documented the effects of dams along the river which can cause alteration of flow condition and the creation of lentic waters above the dam, and also obstruct the movement of fish along the river and alter the taxonomical diversity and the genetic patterns and the functional diversity of fish community (Oliveira et al, 2018;Machado et al, 2022). Unfortunately, in our study, long range migratory fish species, such as the Adriatic sturgeon (Acipenser naccarii), were not sampled in a sufficient number of sites to investigate fragmentation effects on these species and at widest scale.…”
Section: Anthropogenic Pressures In Protected Areasmentioning
confidence: 99%